ECONOMIC AND TECHNOLOGICAL ASPECTS REGARDING THE CULTIVATION OF BLUEBERRIES IN THE CONDITIONS OF THE REPUBLIC OF MOLDOVA - Viorel TURETCHI; Tatiana TURETCHI (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Cultivation of blueberries is an entrepreneurial activity recently approached by local farmers, a business with a fairly high economic potential. The nutritional and economic value of this crop fuels an active interest for both consumers and local producers. However, blueberry cultivation represents a risky challenge for potential domestic producers. This fact is conditioned, mainly, by the local natural factors that are unsuitable for the development and fruiting of the blueberry, respectively, for the creation of conditions similar to the natural habitat of the blueberry, considerable investments are required. The aim of the paper is to present a series of calculations proving that blueberry cultivation represents a profitable business in Moldova. The used methodology is based on comparative, analytical methods, and financial indicators that prove the business profitability. With a thorough elaboration of the whole business process, with all the calculations and analysis of the estimated results, as well as the exact forecasting of the risks and the impact, the cultivation and production of blueberries in the conditions of our country can become a successful business.